THE APPLICATION OF COOPERATIVE LEARNING MODEL OF TYPE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) ON THE MATERIAL OF COMPOSING AN EQUIVALENT FORCE AT CLASS X TECHNIC OF BUILDING CONSTRUCTION SANITATION AND TREATMENT SMK NEGERI 1 PALANGKA RAYA - Shelin Suciana; Yulin Patrisia (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2021)
The research was motivated by the lack of student learning outcomes in the material of composing an equivalent force. Student who less actively involved in the learning process, learning group has not been managed well, the student who is good, medium and low receive equal treatment, not to be rewarded for the best student, good and lowest. The good student very extremely rare to help the weaker students. This research makes use of the quantitative method research and models of type STAD cooperative learning with population student of X technic of building construction sanitation and treatment as many as 28 people. Formulation of the problem in this study is how the application of models of type STAD cooperative learning can improve learning outcomes the material of composing an equivalent force and how the response of student in grade at class X technic of building construction sanitation and treatment SMK Negeri 1 Palangka Raya year 2017/2018. Succesful implementation of type STAD cooperative learning models in the material of composing an equivalent force is to know to an increase and decrease in class X technic of building construction sanitation and treatment of the prior action is pre-test to post-test. In the prior action, the student who can achieve the minimum of criteria competition (KKM) as many as 0 (0%) people with average value are 36.79. At LKS execution in a group, the student who is can achieve the minimum of competition as many as 28(100%) people with the average value is 75,34. At the postest after, students who are complete as many as 15(53.57%) with the average value is 59.88 and completeness level is 53.57%. In a totality value, the student who is complete as many as 15(53.57%) with average value is 65.37 and completeness classical is 53.57%. Although the thoroughness of student increased from the prior action to the finish value or after action, the classical or the overall student learning outcomes have not reached 85% KKM set at 70, on an individual basis there is some student who does not complete. Thus it can be retrieved the conclusion by the application of the model of type STAD cooperative learning can improve learning outcomes in class X technic of building construction sanitation and treatment SMK Negeri 1 Palangka Raya year 2017/2018